2022
DOI: 10.1021/acssuschemeng.2c05534
|View full text |Cite
|
Sign up to set email alerts
|

Waste to Treasure: Regeneration of Porous Co-Based Catalysts from Spent LiCoO2 Cathode Materials for an Efficient Oxygen Evolution Reaction

Abstract: The increasing demand for portable electronic devices and electric vehicles (EVs) has triggered the rapid growth of the rechargeable Li-ion battery (LIB) market. However, in the near future, it is predicted that a large amount of spent LIBs will be scrapped, imposing huge pressure on environmental protection and resource reclaiming. The effective recycling or regeneration of the spent LIBs not only relieves the environmental burdens but also avoids the waste of valuable metal resources. Herein, a porous Co9S8/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Moreover, the peaks at 784.00 and 802.50 eV were assigned as the satellite peaks of Co 2+ . 32,33 Compared to CDC-600, the peaks of Co 3+ 2p 3/2 /2p 1/2 and Co 2+ 2p 3/2 /2p 1/2 in CDC-800 exhibited positive shifts of 0.05/ 0.04 and 0.19/0.30 eV, respectively, and CDC-1000 had positive shifts of 0.14/0.06 and 0.51/0.60 eV, respectively. These results indicate that an increase in the self-vulcanization temperature can enhance the electronic interactions at the Co 1−x S/Co 9 S 8 heterogeneous interface.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, the peaks at 784.00 and 802.50 eV were assigned as the satellite peaks of Co 2+ . 32,33 Compared to CDC-600, the peaks of Co 3+ 2p 3/2 /2p 1/2 and Co 2+ 2p 3/2 /2p 1/2 in CDC-800 exhibited positive shifts of 0.05/ 0.04 and 0.19/0.30 eV, respectively, and CDC-1000 had positive shifts of 0.14/0.06 and 0.51/0.60 eV, respectively. These results indicate that an increase in the self-vulcanization temperature can enhance the electronic interactions at the Co 1−x S/Co 9 S 8 heterogeneous interface.…”
Section: Resultsmentioning
confidence: 96%
“…61 Huang et al 62 reported the transition of spent LiCoO 2 cathode into 2D ultrathin CoOOH nanosheets by using a positive-bias driven exfoliation process due to the synergy of phase conversion and lattice expansion, which exhibited an overpotential of 301 mV@10 mA cm −2 and Tafel slope of 53.8 mV dec −1 . Porous Co 9 S 8 /Co 3 O 4 heterostructure 63 was prepared by a conventional hydrometallurgy and sulfidation process from spent LiCoO 2 cathode, which exhibited an overpotential of 274 mV@10 mA cm −2 and Tafel slope of 48.7 mV dec −1 . Cui et al 64 converted spent LiFePO 4 cathode to defect-rich NiFe oxy/hydroxide catalyst through a wetness impregnation method, and the overpotential at 10 mA cm −2 was 285 mV and Tafel slope was 45 mV dec −1 .…”
Section: Upcycling Of Spent Cathode Materialsmentioning
confidence: 99%
“…The combination of graded porosity and heterostructure promoted OER performance, exhibiting an overpotential of 274 mV at 10 mA cm −2 and a Tafel slope of 48.7 mV. 77 In addition, LiFePO 4 in spent batteries can also be regenerated into efficient electrocatalysts, successfully achieving the functional transformation from battery electrode materials to electrocatalysts. Cui et al adopted a wetness impregnation method to transfer spent LiFePO 4 into a high-performance NiFe oxy/hydroxide OER electrocatalyst.…”
Section: Waste To Wealth In Electrocatalysismentioning
confidence: 99%